2005
DOI: 10.1128/mcb.25.14.6279-6288.2005
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Growth Factor D Is Activated by Urokinase Plasminogen Activator in Prostate Carcinoma Cells

Abstract: Platelet-derived growth factors (PDGFs) regulate a diverse array of cellular processes, including cell proliferation, transformation, migration, survival, and apoptosis of mesenchymal cells, in development as well as during pathogenesis (reviewed in references 31 and 42). For over 2 decades, PDGFs were thought to exist as the homodimers PDGF AA and BB or the heterodimer PDGF AB. These PDGF dimers are processed intracellularly and secreted as active dimers that readily activate PDGF receptors (PDGFRs). Recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
102
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 39 publications
4
102
0
1
Order By: Relevance
“…We have addressed the possibility that cell surface bound complexes of uPA/uPAR regulate activation of PDGF-DD, partly as a result of a locally increased uPA concentration, but also by the prolonged and directed proteolytic activity of uPAR-bound uPA. Consistent with reports showing a prognostic value of uPA and uPAR in suggested PDGF-DD/PDGFRb driven pathologies such as prostate cancer (Miyake et al, 1999;Ustach and Kim, 2005), this proposed mechanism is likely to be beneficial for regulating the efficacy of PDGF-DD activation in the local milieu. Our results confirmed that the presence of uPAR increased PDGF-DD activation by uPA under certain conditions, but also showed that uPAR was not an absolute requirement for the activation to occur.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…We have addressed the possibility that cell surface bound complexes of uPA/uPAR regulate activation of PDGF-DD, partly as a result of a locally increased uPA concentration, but also by the prolonged and directed proteolytic activity of uPAR-bound uPA. Consistent with reports showing a prognostic value of uPA and uPAR in suggested PDGF-DD/PDGFRb driven pathologies such as prostate cancer (Miyake et al, 1999;Ustach and Kim, 2005), this proposed mechanism is likely to be beneficial for regulating the efficacy of PDGF-DD activation in the local milieu. Our results confirmed that the presence of uPAR increased PDGF-DD activation by uPA under certain conditions, but also showed that uPAR was not an absolute requirement for the activation to occur.…”
Section: Discussionsupporting
confidence: 85%
“…Structural determinants required for PDGF-DD activation were further explored by dissecting the importance of the putative cleavage site region. Recently, the introduction of a double mutation (R247A, R249A) in PDGF-D was shown to effectively reduce uPA-mediated activation of PDGF-DD (Ustach and Kim, 2005) and our data more specifically demonstrated that R249A alone is responsible for this reported phenomenon. However, as tPA-induced activation of PDGF-CC is confined to a conserved tribasic site, it is likely that uPA has preferences for a similar site in PDGF-DD.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations